Evaluation of Qatar's First Cardiac Rehabilitation Program: A Brief Report - Eman Faisal; Rahma Saad; Mohammed Al-Hashemi; Sherry L. Grace; Theodoros Papasavvas; Karam Turk-Adawi (Ubiquity Press, 2021)
Background: There are few studies on the impact of cardiac rehabilitation (CR) in the Eastern Mediterranean Region (EMR), where the burden of risk factors and context is somewhat different from Western countries where much of the evidence is derived. Objective: To evaluate patient engagement in, and outcomes associated with, participation in Qatar's first and only CR program, from inception. Methods: This was a retrospective, observational study of patients referred to Heart Hospital's CR program from January 2013-September, 2018. The program offered 3 sessions/week over 6-12 weeks, depending on patient risk. An initial assessment was performed, and outcomes (i.e., functional capacity, risk factors, and psychosocial well-being (quality of life [SF-36] and depressive symptoms) were re-assessed post-program in those who did not drop-out. Session attendance was recorded. Results: 682 patients enrolled; they attended 77.6% of prescribed sessions; 554 (81.2%) completed the program and post-assessment. Improvements in functional capacity were statistically and clinically meaningful (METs 9.3 ± 3.3 pre and 11.1 ± 3.7 post; p < 0.001). There were significant improvements in body mass index (28.7 ± 5.2 kg/m2 pre and 28.2 ± 5.4 post; p < 0.001), waist circumference (102.8 ± 13.0 cm pre and 101.8 ± 13.2 post; p < 0.001), low-density lipoprotein (LDL 1.9 ± 0.9 mmol/L pre and 1.6 ± 0.8 post; p = < 0.001), total cholesterol (3.6 ± 1.1 mmol/L pre and 3.3 ± 0.8 post; p < 0.001), systolic blood pressure (SBP 128.5 ± 17.7 mmHg pre and 123.7 ± 14.8 post; p < 0.001), hemoglobin A1c (6.8 ± 1.6% pre and 6.5 ± 1.3 post; p < 0.001) and depressive symptoms (Cardiac Depression Scale score 78.3 ± 23.9 pre and 66.3 ± 21.3 post; p < 0.001). Improvements on 7 of the 8 quality of life domains were also observed (all p < .05; e.g., physical functioning 68.2 ± 24.0 pre and 74.9 ± 24.4 post). Conclusion: The new Qatari CR program is very engaging to patients, and resulted in clinically significant risk factors (LDL, SBP, and cholesterol) as well as functional capacity and health-related quality of life improvements, which likely translate to reduced morbidity and mortality.